2015
DOI: 10.1080/15384101.2015.1041684
|View full text |Cite
|
Sign up to set email alerts
|

Leptin activation of mTOR pathway in intestinal epithelial cell triggers lipid droplet formation, cytokine production and increased cell proliferation

Abstract: Accumulating evidence suggests that obesity and enhanced inflammatory reactions are predisposing conditions for developing colon cancer. Obesity is associated with high levels of circulating leptin. Leptin is an adipocytokine that is secreted by adipose tissue and modulates immune response and inflammation. Lipid droplets (LD) are organelles involved in lipid metabolism and production of inflammatory mediators, and increased numbers of LD were observed in human colon cancer. Leptin induces the formation of LD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 67 publications
1
56
0
Order By: Relevance
“…Colonic TNF-α expression is elevated in HFD-fed mice [80], and TNF-α is potent inducer of IL-6 which is known to play a role in promoting colorectal cancer [81]. A recent study found that leptin stimulated the production of IL-6 and TNF-α and promoted proliferation in colon epithelial cells in an mTOR-dependent manner [82]. Adiponectin can inhibit colorectal cancer cell growth through activation of AMPK [83], and loss of adiponectin enhances development of both colitis-associated colorectal cancer and in APC min mice [84].…”
Section: Obesity and Cancermentioning
confidence: 99%
“…Colonic TNF-α expression is elevated in HFD-fed mice [80], and TNF-α is potent inducer of IL-6 which is known to play a role in promoting colorectal cancer [81]. A recent study found that leptin stimulated the production of IL-6 and TNF-α and promoted proliferation in colon epithelial cells in an mTOR-dependent manner [82]. Adiponectin can inhibit colorectal cancer cell growth through activation of AMPK [83], and loss of adiponectin enhances development of both colitis-associated colorectal cancer and in APC min mice [84].…”
Section: Obesity and Cancermentioning
confidence: 99%
“…The monocyte chemoattractant protein (MCP‐1, also known as chemokine ligand 2 [CCL2]) is a central chemokine in mononuclear cell recruitment . In different models such as saturated fatty acid‐ or oxLDL‐rich conditions, leptin stimuli in tumor cells, polymicrobial infection, or LPS‐driven inflammatory responses, the increase in MCP‐1/CCL2 production occurs in parallel to LD formation. Indeed, MCP‐1/CCL2 directly induces a dose‐dependent increase in the numbers of cytoplasmic LDs in vitro within resident peritoneal macrophages isolated from naive mice, indicating that its effect occurs through cell migration independent pathways.…”
Section: Ld Biogenesis In Cells Of the Immune Responsementioning
confidence: 99%
“…In a study of normal uterine smooth muscle cells collected from myometrial biopsies, leptin induced cell proliferation at both low and high doses (6.25 and 50 ng/ml) [165]. In the same way, leptin was documented to stimulate the proliferation of normal intestinal epithelial cells (IEC-6 cells) [166]. With regard to the proliferation of cancer cells, the pertinent information has been provided in Table 3 along with a brief etiologic account [116,167180].…”
Section: Leptin In Tumor Progressionmentioning
confidence: 99%